Physiological roles for the subfornical organ: a dynamic transcriptome shaped by autonomic state. (13th October 2015) - Hindmarch, Charles Colin Thomas; Ferguson, Alastair V.
Abstract : This schematic diagram highlights the central role of the subfornical organ (SFO) as a CNS structure without the normal blood brain barrier which plays critical roles in sensing and integrating peripheral signals of body fluid and metabolic status which do not cross the normal blood brain barrier. It highlights the primary outputs of SFO neurons to other CNS autonomic control centres including the arcuate (ARC), paraventricular (PVN), supraoptic (SON), and median preoptic (MnPO) nuclei, as well as the organum vasculosum of the lamina terminalis (OVLT), through which these integrative SFO neurons influence autonomic outputs. This diagram also summarises data from transcriptomic analysis, highlighting the numbers of genes expressed in SFO, the numbers regulated by dehydration and food deprivation, as well as validated and yet to be validated targets. Abstract: The subfornical organ (SFO) is a circumventricular organ recognized for its ability to sense and integrate hydromineral and hormonal circulating fluid balance signals, information which is transmitted to central autonomic nuclei to which SFO neurons project. While the role of SFO was once synonymous with physiological responses to osmotic, volumetric and cardiovascular challenge, recent data suggest that SFO neurons also sense and integrate information from circulating signals of metabolic status. Using microarrays, we have confirmed the expression of receptors already described in the SFO, and identified many novel transcripts expressed in this circumventricular organ including receptors for many of the critical circulating energy balance signals such as adiponectin, apelin, endocannabinoids, leptin, insulin and peptide YY. This transcriptome analysis also identified SFO transcripts, the expressions of which are significantly changed by either 72 h dehydration, or 48 h starvation, compared to fed and euhydrated controls. Expression and potential roles for many of these targets are yet to be confirmed and elucidated. Subsequent validation of data for adiponectin and leptin receptors confirmed that receptors for both are expressed in the SFO, that discrete populations of neurons in this tissue are functionally responsive to these adipokines, and that such responsiveness is regulated by physiological state. Thus, transcriptomic analysis offers great promise for understanding the integrative complexity of these physiological systems, especially with development of technologies allowing description of the entire transcriptome of single, carefully phenotyped, SFO neurons. These data will ultimately elucidate mechanisms through which these uniquely positioned neurons respond to and integrate complex circulating signals.